AN ANALYSIS OF FEATURES AND FUNCTIONS IN WOMEN’S SPEECH IN THE TALKSHOW UNITED STATES OF WOMEN SUMMIT - Alika Putri Badari; Agnes Setyowati H; Ni Made Widisanti S (Journal Albion : Journal of English Literature, Language, and Culture, 2019)
AbstractThis study aims at denoting the features of female speech and its functions that Michelle Obama applied in the Talk Show United States of Women Summit. In addition, the purpose of this study is to also denote the features of male speech, so as to see which feature is the most dominant in use. The study results in the finding of 18 data of women's utterances. There are 7 types of speech features consisting of 2 data adjectives, 1 datum of tag question, 2 data of raising intonations on declaratives, 1 datum of avoidance of strong swear words, 6 data of emphatic stress, 2 data of lexical hedges and 3 data of intensifiers. The female speech features in the analysis serve as hedges device and booster device. The present writer also sees that Michelle uses two types of male speech features in 4 data, they are 3 pieces of minimal responses and 1 command and directive. Therefore, it can be said that the use of female speech features in this research are more dominant than male's.Keywords: men’s speech features, women’s speech features, functions of women’s speech features.